Synthesis of zirconocene complexes and their use in slurry-phase polymerisation of ethylene - Angpanitcharoen, P; Lamb, JV; Buffet, J-C; Turner, ZR; O'Hare, D (Royal Society of Chemistry, 2021)
A new family of zirconocene complexes of the type (3-RInd#)2ZrX2 (where Ind# = C6Me5H and R = Me, Et and Ph) have been synthesised and fully characterised. Six new crystal structures have been reported (meso-(3-EtInd#)2ZrBr2, rac-(3-EtInd#)2ZrCl2, rac-(3-EtInd#)2Zr(CH2Ph)2, meso-(3-EtInd#)2Zr(CH2Ph)2, meso-(3-MeInd#)2ZrBr2 and meso-(3-MeInd#)2Zr(CH2Ph)2). The complexes were studied for slurry-phase ethylene polymerisation when immobilised on solid polymethylaluminoxane (sMAO). Variation in the initiation group was found to have greater influence over polymerisation activity for meso-catalysts than rac-catalysts, with meso-alkyl catalysts showing higher polymerisation activities than meso-halide. Below 70 °C, polymerisation activity follows the order sMAO-meso-(3-EtInd#)2Zr(CH2Ph)2, sMAO-meso-(3-EtInd#)2ZrCl2 and sMAO-meso-(3-EtInd#)2ZrBr2 (activities of 657, 561, and 452 kgPE molM−1 h−1 bar−1, respectively). sMAO-meso-(3-EtInd#)2ZrBr2 produces HDPE with the highest molecular weight, followed by sMAO-meso-(3-EtInd#)2ZrCl2 and sMAO-meso-(3-EtInd#)2Zr(CH2Ph)2 (Mw of 503, 406, and 345 kg mol−1, respectively, at 50 °C). sMAO-meso-(3-MeInd#)2ZrBr2 produced HDPE with almost identical molecular weights to sMAO-meso-(3-EtInd#)2ZrCl2 (395 kg mol−1 at 50 °C).